Long-term prognosis analysis of PARACHUTE device implantation in patients with ischemic heart failure: a single-center experience of Chinese patients - Li, Jianghua; Liu, Huadong; Liu, Qiyun; Liu, Cheng; Xiong, Wei; Ma, Wei; Zhang, Baowei; Dong, Shaohong; Li, Tangzhiming (Journal of cardiothoracic surgery, 2021)
Heart failure (HF) is one of the leading causes of mortality and morbidity. The PARACHUTE device is designed to partition for left ventricular (LV) apical aneurysm post extensive anterior myocardial infarction (MI). However, the long-term prognosis of the PARACHUTE device post-implantation is unclear. From November 2015 to April 2017, six subjects with New York Heart Association Classes II, III and IV ischemic HF, LV ejection fraction between (LVEF) 15 and 40%; and LV anterior apical aneurysm were enrolled in our center. The cumulative event rates for MI, hospitalization, and mortality were documented. Further assessment of LVEF, LV end-diastolic diameter (LVEDD), and estimated pulmonary artery pressure were determined by echocardiography core laboratory. For quantitative data comparison, paired t-test was employed. Device implantation was successful in all six enrolled subjects, and acute device association adverse events were not observed. At 4.6 ± 1.7 years follow-up, major adverse cardiac events (MACEs) were found in 50% patients, and the survival rate was 86.7%. We observed that the LVEF was significantly elevated after deployment (46.00 ± 6.00% vs. 35.83 ± 1.47%, P = 0.009). Besides, the LVEDD elevated after MI (51.17 ± 3.71 vs. 62.83 ± 3.25, P < 0.001) was revealed, but the device sustained preserved LVEDD after implantation. The PARACHUTE device is an alternative therapy for patients with severe LV maladaptive remodeling. However, the device seems to increase the HF ratio. NCT02240940.